The Effect of Using Crossword Puzzle Educational Games on the Motivation and Academic Achievement of Grade XI Students at SMAN 10 Makassar - Nur Arisah; Muh. Rizah Putrawan (International journal of technology and education research, 2026)
This study examines the influence of the Crossword Puzzle educational game on the learning outcomes and motivation of class XI Economics students at SMAN 10 Makassar. Data were collected through observation, interviews, and recording using qualitative methods and a descriptive approach. The research was conducted directly at the location of SMAN 10 Makassar, class XI IPS 5 with a total of 37 students. The research findings show that the use of Crossword Puzzles media increases student motivation and performance. Learning that was previously boring, but after using Crossword Puzzles, children become more active and enthusiastic. The use of Crossword Puzzles educational games improves learning outcomes, fosters a dynamic learning environment, and helps students understand the subject matter.